2011
DOI: 10.1039/c1cp21899a
|View full text |Cite
|
Sign up to set email alerts
|

The cages, dynamics, and structuring of incipient methane clathrate hydrates

Abstract: Interest in describing clathrate hydrate formation mechanisms spans multiple fields of science and technical applications. Here, we report findings from multiple molecular dynamics simulations of spontaneous methane clathrate hydrate nucleation and growth from fully demixed and disordered two-phase fluid systems of methane and water. Across a range of thermodynamic conditions and simulation geometries and sizes, a set of seven cage types comprises approximately 95% of all cages formed in the nucleated solids. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
144
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(166 citation statements)
references
References 57 publications
22
144
0
Order By: Relevance
“…For instance, in simulations it is quite commonly observed that in addition to the thermodynamically stable phase that is observed during synthetic procedures other metastable hydrate phases are formed [46,47,36], in agreement to the appearance of mixed phases in modeling studies. In other experiments where nucleation and growth takes place rather slowly (min/h), cage populations can be measured as a function of time.…”
Section: Nucleationmentioning
confidence: 60%
See 1 more Smart Citation
“…For instance, in simulations it is quite commonly observed that in addition to the thermodynamically stable phase that is observed during synthetic procedures other metastable hydrate phases are formed [46,47,36], in agreement to the appearance of mixed phases in modeling studies. In other experiments where nucleation and growth takes place rather slowly (min/h), cage populations can be measured as a function of time.…”
Section: Nucleationmentioning
confidence: 60%
“…2 [35]. Recent work demonstrated that the stable sI clathrate hydrate structure can be obtained from some trajectories of the homogeneous nucleation simulation [36,37]. Increased curvature of the water-gas interface was shown to increase the rate of clathrate hydrate nucleation [30].…”
Section: Nucleationmentioning
confidence: 99%
“…5,28,29 Radhakrishnan and Trout defined a further order parameter based on the number of guests at a suitable distance from the central one, i.e., within the domain of the first peak of the guest-guest pair correlation function of hydrates. 4 Further, geometric hydrate-liquid recognition criteria have focussed on identification of hydrate-like cavities, either polyhedral (i.e., 5 12 , 5 12 6 2 , 5 12 6 3 , or 5 12 6 4 ) 10,16,30,31 or halfpolyhedral (i.e., 5 6 , 5 6 6 1 , or 5 6 6 2 ). 32 Chakraborty et al defined Voronoi tessellation of the space centred around guest molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Ice nuclei are almost solely comprised of double-diamond and hexagonal water cages as illustrated in figures 5 and 6 of ref. 19, whereas hydrate nuclei contain many more different types of water cages (25,26,35). From the perspective of combinatorics, there are many more possible hydrogen-bond structures for hydrate nuclei than there are for ice nuclei.…”
mentioning
confidence: 99%